Serum osteoprotegerin in young survivors of myocardial infarction - Vik, Anders; Brodin, Ellen; Børvik, Trond; Sveinbjørnsson, Baldur; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2006)
Osteoprotegerin (OPG) is a member of the tumour necrosis factor superfamily and is involved in the regulation of bone metabolism and vascular calcification. Increased serum OPG levels have been reported in patients with stable angina pectoris and survivors of myocardial infarction with heart failure. The purpose of the present study was to determine serum OPG levels in young survivors of acute myocardial infarction (MI), and the relationship between OPG, homocysteine, sCD40L and coagulation factors in blood. Fifty-eight patients with verified MI, 40–60 years of age, were recruited 1–4 years after the acute event into an age- and sex- matched case control study with controls recruited from the general population. Serum OPG levels were similar in cases (2.41 ng/ml, 2.11–2.77 ng/ml) (mean, 95% CI) and controls (2.43 ng/ml, 2.11–2.79 ng/ml) (p= 0.92). Significant correlation between OPG and homocysteine was found in patients (r=0.30, p=0.02) and controls (r=0.35, p=0.007). A significant negative correlation was found between OPG and sCD40L in patients (r=-0.51, p<0.001), but not in controls (r=0.001, p=0.96). No associations were found between serum OPG and markers of coagulation activation. The present study shows that serum OPG level was not increased in young survivors of uncomplicated myocardial infarction. Serum OPG levels were not associated with thrombin generation assessed by thrombin-antithrombin complexes (TAT), but a positive association between serum OPG and homocysteine was found.
Keywords: Osteoprotegerin; homocysteine; coagulation; thrombin generation; myocardial infarction